PENERAPAN ANGGARAN BERBASIS KINERJA (PERFORMANCE BASED BUDGETING) DALAM PENGELOLAAN KEUANGAN DAERAH ACEH - Yulia, Ananta; Ningsih, Endang Surasetyo (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2020)
Performance-based budgeting aims to show the relationship between funding and performance to be achieved, increase efficiency and transparency in budgeting, increase flexibility and accountability of units in carrying out tasks and budget management. This study aims to: (1) Know the system of implementing performance- based budgeting in the management of regional finances in the Aceh Work Unit (SKPA) and (2) Knowing the obstacles faced in implementing a performance-based budgeting system in the management of Aceh's regional finances. This research uses a qualitative approach and descriptive research type. The population in this study were all (42) Aceh Work Unit (SKPA) which is the organizer of government activities to manage regional finances. The sample in this study is the entire population (total sample). Data collection uses structured interview techniques. Data were analyzed qualitatively. The results of the study show that: (1) Performance-based budgeting system implementation in regional financial management in the Aceh Work Unit (SKPA) is in accordance with applicable regulations both from the RPJMA that refers to the RPJN until the final process of the birth of the DPA SKPA and with the Aceh Government Performance Report and (2) Constraints faced in implementing a performance-based budgeting system in the management of Aceh's regional finances are internal, such as the limitations of Human Resources (HR) in the budget and external fields such as rewards and punishments from local governments to improve the performance of their employees. Conclusions: (1) Performance-based budgeting system implementation in regional financial management in the Aceh Apparatus Work Unit (SKPA) is in accordance with applicable regulations (2) Constraints faced in implementing performance-based budgeting system in Aceh regional financial management are both internal and internal external.